I Wrote to the Quandt Family and Their Descendants in 1756. Genealogy of the Family Published in the Obituary for Quandt (1772) - Strockis, Mindaugas; Citavičiūtė, Liucija (Senoji Lietuvos literatūra, 2024)
-
Keywords: -